Cost effectiveness of COX 2 selective inhibitors and traditional NSAIDs alone or in combination with a proton pump inhibitor for people with osteoarthritis. (14th July 2009) - Latimer, Nicholas; Lord, Joanne; Grant, Robert L; O'Mahony, Rachel; Dickson, John; Conaghan, Philip G
Abstract : Objectives To investigate the cost effectiveness of cyclo-oxygenase-2 (COX 2) selective inhibitors and traditional non-steroidal anti-inflammatory drugs (NSAIDs), and the addition of proton pump inhibitors to these treatments, for people with osteoarthritis. Design An economic evaluation using a Markov model and data from a systematic review was conducted. Estimates of cardiovascular and gastrointestinal adverse events were based on data from three large randomised controlled trials, and observational data were used for sensitivity analyses. Efficacy benefits from treatment were estimated from a meta-analysis of trials reporting total Western Ontario and McMaster Universities (WOMAC) osteoarthritis index score. Other model inputs were obtained from the relevant literature. The model was run for a hypothetical population of people with osteoarthritis. Subgroup analyses were conducted for people at high risk of gastrointestinal or cardiovascular adverse events. Comparators Licensed COX 2 selective inhibitors (celecoxib and etoricoxib) and traditional NSAIDs (diclofenac, ibuprofen, and naproxen) for which suitable data were available were compared. Paracetamol was also included, as was the possibility of adding a proton pump inhibitor (omeprazole) to each treatment. Main outcome measures The main outcome measure was cost effectiveness, which was based on quality adjusted life years gained. Quality adjusted life year scores were calculated from pooled estimates of efficacy and major adverse events (that is, dyspepsia; symptomatic ulcer; complicated gastrointestinal perforation, ulcer, or bleed; myocardial infarction; stroke; and heart failure). Results Addition of a proton pump inhibitor to both COX 2 selective inhibitors and traditional NSAIDs was highly cost effective for all patient groups considered (incremental cost effectiveness ratio less than £1000 (€1175, 1650)). This finding was robust across a wide range of effectiveness estimates if the cheapest proton pump inhibitor was used. In our base case analysis, adding a proton pump inhibitor to a COX 2 selective inhibitor (used at the lowest licensed dose) was a cost effective option, even for patients at low risk of gastrointestinal adverse events (incremental cost effectiveness ratio approximately £10 000). Uncertainties around relative adverse event rates meant relative cost effectiveness for individual COX 2 selective inhibitors and traditional NSAIDs was difficult to determine. Conclusions Prescribing a proton pump inhibitor for people with osteoarthritis who are taking a traditional NSAID or COX 2 selective inhibitor is cost effective. The cost effectiveness analysis was sensitive to adverse event data and the specific choice of COX 2 selective inhibitor or NSAID agent should, therefore, take into account individual cardiovascular and gastrointestinal risks.